(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
This article explores modern didactic approaches that effectively engage pupils in the physics learning process. It discusses problem-based learning, interactive methods, project-based instruction, and the integration of digital technologies. Practical examples are used to demonstrate how these strategies enhance pupils’ critical thinking, inquiry skills, and interest in physics education.